2011
DOI: 10.1273/cbij.11.41
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of MAP kinase PTC1 mutant exposed to deoxynivalenol

Abstract: Deoxynivalenol (DON) is a secondary metabolite that is generated by Fusarium species, which seriously affects both humans and livestock. Protein synthesis inhibition and ribotoxic stress, caused by induction of the mitogen activated protein kinase (MAPK) cascade, are thought to be responsible for the majority of DON toxicity. However, as DNA damage has also been reported, it is necessary to clarify all sources of toxicity. In this study, we conducted a DON exposure test using the PTC1 yeast mutant with disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Results from each study showed that the toxicity of each mycotoxin generally aligned with that reported for animal cell systems, indicating that yeast cells can be used as an easy-to-handle eukaryotic cell evaluation system. For the evaluation of AFB 1 , the Saccharomyces cerevisiae BY4743 ptc1 mutant strain, lacking the beta-1,3-glucan synthesis gene, was used [4]. This mutation results in the loss of repressive control of the mitogen-activated protein kinase pathway, indirectly altering the expression of phosphoenolpyruvate carboxykinase, leading oxaloacetate in the tricarboxylic acid (TCA) cycle to the glycogenic pathway.…”
Section: Toxicity Evaluations Of Major Mycotoxinsmentioning
confidence: 99%
“…Results from each study showed that the toxicity of each mycotoxin generally aligned with that reported for animal cell systems, indicating that yeast cells can be used as an easy-to-handle eukaryotic cell evaluation system. For the evaluation of AFB 1 , the Saccharomyces cerevisiae BY4743 ptc1 mutant strain, lacking the beta-1,3-glucan synthesis gene, was used [4]. This mutation results in the loss of repressive control of the mitogen-activated protein kinase pathway, indirectly altering the expression of phosphoenolpyruvate carboxykinase, leading oxaloacetate in the tricarboxylic acid (TCA) cycle to the glycogenic pathway.…”
Section: Toxicity Evaluations Of Major Mycotoxinsmentioning
confidence: 99%